Life-Cycle Management Strategy on Steel Girders in Bridges - Kevin K. L. So; Moe M. S. Cheung; Eric X. Q. Zhang (Advances in Civil Engineering)
The major problems affecting the service life of bridges are related to various factors such as fatigue-sensitive details, increased service loads, corrosion deterioration, and the lack of proper maintenance. Among them, corrosion deterioration and fatigue damages of structures particularly to steel girder bridges are the most common ones. Bridges of different structural forms, at different locations or under different climates, may suffer from various degrees of deterioration. Steel girders at different positions of a bridge may also suffer from different degrees of damage. How to effectively maintain the bridge asset at a minimal cost and how to predict the time for future works are crucial, particularly when government funding sources become stretched. A comprehensive bridge management framework assisting stakeholders to appropriately and reasonably prioritize their future maintenance-related works in their bridge stocks, such that stakeholders can better allocate the limited resources, is utmost concerned. This paper proposes an integrated life-cycle management (LCM) strategy on steel girders in bridges in which corrosion deterioration and fatigue damage prediction models are mapped with girders’ performance conditions. A practical example to demonstrate the applicability of the proposed LCM strategy is also illustrated.